X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=week2.mdwn;h=b23d1a74efb87fabd5bda7a89ce16e9f3406a9d0;hp=80f3946591d78ea0c7a0b6021e9614292a8e6194;hb=d1761bf08a977c86230b82fbd4b9da0c7b940d78;hpb=4556367eaeb7208a675bc17158418acc013149f6 diff --git a/week2.mdwn b/week2.mdwn index 80f39465..b23d1a74 100644 --- a/week2.mdwn +++ b/week2.mdwn @@ -1,3 +1,6 @@ +[[!toc]] + + Syntactic equality, reduction, convertibility ============================================= @@ -6,6 +9,13 @@ Define T to be (\x. x y) z. Then T and (\x. x y) z are syntactically equal,
T ≡ (\x. x y) z ≡ (\z. z y) z

+[Fussy note: the justification for counting (\x. x y) z as +equivalent to (\z. z y) z is that when a lambda binds a set of +occurrences, it doesn't matter which variable serves to carry out the +binding. Either way, the function does the same thing and means the +same thing. Look in the standard treatments for discussions of alpha +equivalence for more detail.] + This: T ~~> z y @@ -23,21 +33,169 @@ Lambda expressions that have no free variables are known as **combinators**. Her > **I** is defined to be \x x -> **K** is defined to be \x y. x, That is, it throws away its second argument. So K x is a constant function from any (further) argument to x. ("K" for "constant".) Compare K to our definition of **true**. +> **K** is defined to be \x y. x. That is, it throws away its + second argument. So K x is a constant function from any + (further) argument to x. ("K" for "constant".) Compare K + to our definition of true. + +> **get-first** was our function for extracting the first element of an ordered pair: \fst snd. fst. Compare this to K and true as well. + +> **get-second** was our function for extracting the second element of an ordered pair: \fst snd. snd. Compare this to our definition of false. + +> **B** is defined to be: \f g x. f (g x). (So B f g is the composition \x. f (g x) of f and g.) -> **get-first** was our function for extracting the first element of an ordered pair: \fst snd. fst. Compare this to **K** and **true** as well. +> **C** is defined to be: \f x y. f y x. (So C f is a function like f except it expects its first two arguments in swapped order.) -> **get-second** was our function for extracting the second element of an ordered pair: \fst snd. snd. Compare this to our definition of **false**. +> **W** is defined to be: \f x . f x x. (So W f accepts one argument and gives it to f twice. What is the meaning of W multiply?) -> **ω** is defined to be: \x. x x +> **ω** (that is, lower-case omega) is defined to be: \x. x x It's possible to build a logical system equally powerful as the lambda calculus (and readily intertranslatable with it) using just combinators, considered as atomic operations. Such a language doesn't have any variables in it: not just no free variables, but no variables at all. One can do that with a very spare set of basic combinators. These days the standard base is just three combinators: K and I from above, and also one more, **S**, which behaves the same as the lambda expression \f g x. f x (g x). behaves. But it's possible to be even more minimalistic, and get by with only a single combinator. (And there are different single-combinator bases you can choose.) -These systems are Turing complete. In other words: every computation we know how to describe can be represented in a logical system consisting of only a single primitive operation! +There are some well-known linguistic applications of Combinatory +Logic, due to Anna Szabolcsi, Mark Steedman, and Pauline Jacobson. +Szabolcsi supposed that the meanings of certain expressions could be +insightfully expressed in the form of combinators. + + +For instance, Szabolcsi argues that reflexive pronouns are argument +duplicators. + +![reflexive](http://lambda.jimpryor.net/szabolcsi-reflexive.jpg) + +Notice that the semantic value of *himself* is exactly W. +The reflexive pronoun in direct object position combines first with the transitive verb (through compositional magic we won't go into here). The result is an intransitive verb phrase that takes a subject argument, duplicates that argument, and feeds the two copies to the transitive verb meaning. + +Note that W <~~> S(CI): + +
S(CI) ≡
+S((\fxy.fyx)(\x.x)) ~~>
+S(\xy.(\x.x)yx) ~~>
+S(\xy.yx) ≡
+(\fgx.fx(gx))(\xy.yx) ~~>
+\gx.(\xy.yx)x(gx) ~~>
+\gx.(gx)x ≡
+W
+ +Ok, here comes a shift in thinking. Instead of defining combinators as equivalent to certain lambda terms, +we can define combinators by what they do. If we have the I combinator followed by any expression X, +I will take that expression as its argument and return that same expression as the result. In pictures, + + IX ~~> X + +Thinking of this as a reduction rule, we can perform the following computation + + II(IX) ~~> IIX ~~> IX ~~> X + +The reduction rule for K is also straightforward: + + KXY ~~> X + +That is, K throws away its second argument. The reduction rule for S can be constructed by examining +the defining lambda term: + + S = \fgx.fx(gx) + +S takes three arguments, duplicates the third argument, and feeds one copy to the first argument and the second copy to the second argument. So: + + SFGX ~~> FX(GX) + +If the meaning of a function is nothing more than how it behaves with respect to its arguments, +these reduction rules capture the behavior of the combinators S, K, and I completely. +We can use these rules to compute without resorting to beta reduction. For instance, we can show how the I combinator is equivalent to a certain crafty combination of Ss and Ks: + + SKKX ~~> KX(KX) ~~> X + +So the combinator SKK is equivalent to the combinator I. + +Combinatory Logic is what you have when you choose a set of combinators and regulate their behavior with a set of reduction rules. The most common system uses S, K, and I as defined here. + +###The equivalence of the untyped lambda calculus and combinatory logic### + +We've claimed that Combinatory Logic is equivalent to the lambda calculus. If that's so, then S, K, and I must be enough to accomplish any computational task imaginable. Actually, S and K must suffice, since we've just seen that we can simulate I using only S and K. In order to get an intuition about what it takes to be Turing complete, imagine what a text editor does: +it transforms any arbitrary text into any other arbitrary text. The way it does this is by deleting, copying, and reordering characters. We've already seen that K deletes its second argument, so we have deletion covered. S duplicates and reorders, so we have some reason to hope that S and K are enough to define arbitrary functions. + +We've already established that the behavior of combinatory terms can be perfectly mimicked by lambda terms: just replace each combinator with its equivalent lambda term, i.e., replace I with \x.x, replace K with \fxy.x, and replace S with \fgx.fx(gx). How about the other direction? Here is a method for converting an arbitrary lambda term into an equivalent Combinatory Logic term using only S, K, and I. Besides the intrinsic beauty of this mapping, and the importance of what it says about the nature of binding and computation, it is possible to hear an echo of computing with continuations in this conversion strategy (though you would be able to hear these echos until we've covered a considerable portion of the rest of the course). + +Assume that for any lambda term T, [T] is the equivalent combinatory logic term. The we can define the [.] mapping as follows: + + 1. [a] a + 2. [(M N)] ([M][N]) + 3. [\a.a] I + 4. [\a.M] KM assumption: a does not occur free in M + 5. [\a.(M N)] S[\a.M][\a.N] + 6. [\a\b.M] [\a[\b.M]] + +It's easy to understand these rules based on what S, K and I do. The first rule says +that variables are mapped to themselves. +The second rule says that the way to translate an application is to translate the +first element and the second element separately. +The third rule should be obvious. +The fourth rule should also be fairly self-evident: since what a lambda term such as \x.y does it throw away its first argument and return y, that's exactly what the combinatory logic translation should do. And indeed, Ky is a function that throws away its argument and returns y. +The fifth rule deals with an abstract whose body is an application: the S combinator takes its next argument (which will fill the role of the original variable a) and copies it, feeding one copy to the translation of \a.M, and the other copy to the translation of \a.N. Finally, the last rule says that if the body of an abstract is itself an abstract, translate the inner abstract first, and then do the outermost. (Since the translation of [\b.M] will not have any lambdas in it, we can be sure that we won't end up applying rule 6 again in an infinite loop.) + +[Fussy notes: if the original lambda term has free variables in it, so will the combinatory logic translation. Feel free to worry about this, though you should be confident that it makes sense. You should also convince yourself that if the original lambda term contains no free variables---i.e., is a combinator---then the translation will consist only of S, K, and I (plus parentheses). One other detail: this translation algorithm builds expressions that combine lambdas with combinators. For instance, the translation of \x.\y.y is [\x[\y.y]] = [\x.I] = KI. In that intermediate stage, we have \x.I. It's possible to avoid this, but it takes some careful thought. See, e.g., Barendregt 1984, page 156.] + +Here's an example of the translation: + + [\x\y.yx] = [\x[\y.yx]] = [\x.S[\y.y][\y.x]] = [\x.(SI)(Kx)] = S[\x.SI][\x.Kx] = S(K(SI))(S[\x.K][\x.x]) = S(K(SI))(S(KK)I) + +We can test this translation by seeing if it behaves like the original lambda term does. +The orginal lambda term lifts its first argument (think of it as reversing the order of its two arguments): + + S(K(SI))(S(KK)I) X Y = + (K(SI))X ((S(KK)I) X) Y = + SI ((KK)X (IX)) Y = + SI (KX) Y = + IY (KX)Y = + Y X + +Viola: the combinator takes any X and Y as arguments, and returns Y applied to X. + +Back to linguistic applications: one consequence of the equivalence between the lambda calculus and combinatory +logic is that anything that can be done by binding variables can just as well be done with combinators. +This has given rise to a style of semantic analysis called Variable Free Semantics (in addition to +Szabolcsi's papers, see, for instance, +Pauline Jacobson's 1999 *Linguistics and Philosophy* paper, Towards a variable-free Semantics'). +Somewhat ironically, reading strings of combinators is so difficult that most practitioners of variable-free semantics +express there meanings using the lambda-calculus rather than combinatory logic; perhaps they should call their +enterprise Free Variable Free Semantics. + +A philosophical application: Quine went through a phase in which he developed a variable free logic. + + Quine, Willard. 1960. Variables explained away. {\it Proceedings of + the American Philosophical Society}. Volume 104: 343--347. Also in + W.~V.~Quine. 1960. {\it Selected Logical Papers}. Random House: New + York. 227--235. + +The reason this was important to Quine is similar to the worries that Jim was talking about +in the first class in which using non-referring expressions such as Santa Clause might commit +one to believing in non-existant things. Quine's slogan was that to be is to be the value of a variable'. +What this was supposed to mean is that if and only if an object could serve as the value of some variable, we +are committed to recognizing the existence of that object in our ontology. +Obviously, if there ARE no variables, this slogan has to be rethought. + +Quine did not appear to appreciate that Shoenfinkel had already invented combinatory logic, though +he later wrote an introduction to Shoenfinkel's key paper reprinted in Jean +van Heijenoort (ed) 1967 *From Frege to Goedel, + a source book in mathematical logic, 1879--1931*. +Cresswell has also developed a variable-free approach of some philosophical and linguistic interest +in two books in the 1990's. + +A final linguistic application: Steedman's Combinatory Categorial Grammar, where the "Combinatory" is +from combinatory logic (see especially his 2000 book, *The Syntactic Process*). Steedman attempts to build +a syntax/semantics interface using a small number of combinators, including T = \xy.yx, B = \fxy.f(xy), +and our friend S. Steedman used Smullyan's fanciful bird +names for the combinators, Thrush, Bluebird, and Starling. + +Many of these combinatory logics, in particular, the SKI system, +are Turing complete. In other words: every computation we know how to describe can be represented in a logical system consisting of only a single primitive operation! -Here's more to read about combinatorial logic: +Here's more to read about combinatorial logic. +Surely the most entertaining exposition is Smullyan's [[!wikipedia To_Mock_a_Mockingbird]]. +Other sources include * [[!wikipedia Combinatory logic]] at Wikipedia * [Combinatory logic](http://plato.stanford.edu/entries/logic-combinatory/) at the Stanford Encyclopedia of Philosophy @@ -48,7 +206,7 @@ Here's more to read about combinatorial logic: -Evaluation strategies and Normalization +Evaluation Strategies and Normalization ======================================= In the assignment we asked you to reduce various expressions until it wasn't possible to reduce them any further. For two of those expressions, this was impossible to do. One of them was this: @@ -161,7 +319,8 @@ One important advantage of normal-order evaluation in particular is that it can Indeed, it's provable that if there's *any* reduction path that delivers a value for a given expression, the normal-order evalutation strategy will terminate with that value. -An expression is said to be in **normal form** when it's not possible to perform any more reductions. (EVEN INSIDE ABSTRACTS?) There's a sense in which you *can't get anything more out of* ω ω, but it's not in normal form because it still has the form of a redex. +An expression is said to be in **normal form** when it's not possible to perform any more reductions (not even inside abstracts). +There's a sense in which you *can't get anything more out of* ω ω, but it's not in normal form because it still has the form of a redex. A computational system is said to be **confluent**, or to have the **Church-Rosser** or **diamond** property, if, whenever there are multiple possible evaluation paths, those that terminate always terminate in the same value. In such a system, the choice of which sub-expressions to evaluate first will only matter if some of them but not others might lead down a non-terminating path.